Pengaruh Structured Group Exercise Program terhadap Kualitas Hidup Lansia di Paguyuban Lansia RW 08 Kemiri, Kebakkramat, Karanganyar - Safitri, Rina; Puspitosari, Aniek (Jurnal Terapi Wicara dan Bahasa, 2024)
Abstract Background: The elderly are an age group where every individual experiences health problems, both physical, cognitive and psychosocial. These health problems will cause a decrease in the quality of life in the elderly. Therefore, interventions are needed aimed at minimizing the decline in the quality of life of the elderly. Structured Group Exercise Program (SGEP) is an intervention in the form of planned physical exercise, repetitive and consistent body movements to improve or maintain one or more components of physical fitness. Objectives: This research aims to determine the effect of SGEP on the quality of life of the elderly in the elderly community RW 08 Desa Kemiri, Kecamatan Kebakkramat, Kabupaten Karanganyar. Methods: This research is a quantitative Pre-Experimental Design research with one group pre-post test type. The research was conducted at the elderly community RW 08 Desa Kemiri, Kecamatan Kebakkramat, Kabupaten Karanganyar. The sampling technique used purposive sampling with a total of 27 samples. The research instrument used was the World Health Organization Quality of Life (WHOQOL-BREF). The SGEP intervention was carried out in 8 sessions over 8 weeks. Data analysis used a paired t-test which was processed using SPSS version 25. Results:. The sample for this study was 100% female. Other characteristics were dominated by the elderly age group (59.3%), family status was dominated by the sample living with family (85.2%), and employment was dominated by the non-working sample (59.3%). The results of the paired sample t-test obtained Asmyp Sig. (2-tailed) = 0.000, which means p-value < α (0.05). Conclusion: There is an effect of providing the Structured Group Exercise Program (SGEP) intervention on the quality of life of the elderly in the elderly community RW 08 Desa Kemiri, Kecamatan Kebakkramat, Kabupaten Karanganyar. Keywords: Structured Group Exercise Program, Quality of Life, Elderly